Population Density and Diversity of Macrozoobenthos in Seagrass Ecosystems in the Coastal Area of Tablolong Village - Chaterina A. Paulus; Aludin Al Ayubi; Lebrina I. Boikh; Suprabadevi Saraswati; Emil Azmanajaya (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
The presence of macrozoobenthos associated with seagrass ecosystems plays an important role in ecological systems and bioindicators for water quality assessment. This study aims to determine the density and diversity of macrozoobenthos populations in seagrass ecosystems in the tourism area in the coastal area of Tablolong village, West Kupang district, Kupang regency. The data collection method in this study was the observation method using the quadrant transect technique. The data collected in this study were analyzed using qualitative and quantitative descriptive analysis. The findings of this study revealed 38 macrozoobenthos species including Hemicantrotus pulcherimus, Tripneustes gratilla, Echinotrix sp, Echinometra sp, Diadema setosum, Holthuria atra, Synapta macullata, Holothuria edulis, Archaster typicus, Protoreaster nodosus, Heniricia sp, Ophiotrix sp, Paguristes cadenati, Coenobita rugosus, Portunus sp, Eurynoma aspera, Calappa hepatica, Trocus sp, Strombus luhuanus, Lambis-lambis, Strombus gibherulis, Strombus urceus, Strombus costatus, Cypraea trigis, Cypraea errones, Euspira sp, Cymatium sp, Vexillum sp, Amoria sp, Conus marmoreus, Conus colubrinus, Jorunna parva, Fragrum sp, Frachycardium sp, Maetra sp, Pina sp, Xenophora sp, and Andara antiquate, then population densities between 25.47-59.93 ind/m² with an average value of 44.0 ind/m² or in the low category, as well as the diversity value ranging from 0.317-0.368 with an average value of 0.348 or also in the low category.